The impact of the top management team faultlines on environment, social and governance performance of listed companies - Chen, Xiaofang; Chen, Xin; Fang, Ming; Xia, Wenlei; Hu, Yu (Technological and Economic Development of Economy, 2023)
At present, the research focus on Environment, Social and Governance (ESG) is mainly on the economic consequences of ESG performance, and research on the influencing factors of ESG overall performance is lacking. The top management team plays a decisive role in the decision of ESG investment. To improve ESG performance and promote sustainable development of enterprises. This research explores the influence of different types of top management team faultlines on the ESG performance by using the panel fixed effects model from 2015 to 2019 for the samples of 347 listed enterprises in China, and tests the moderating effect of management incentives. Results show that the relationship-type top management team faultlines is positively correlated with the ESG performance, whereas the task-type faultlines is negatively correlated with the ESG performance. Management compensation incentive will weaken the positive effect of the relationship-type faultlines on the ESG performance, and the moderating effect of the task-type faultlines on the ESG performance is insignificant. Management equity incentive will strengthen the positive effect of the relationship-type faultlines on the ESG performance and weaken the negative effect of the task-type faultlines. Our findings provide a new perspective for how to improve the ESG performance of listed companies by the optimization of corporate governance structure.